Antiradical activity of novel 4-amino-5-(thiophen-2-ylmethyl)- 4H-1,2,4-triazole-3-thiol derivatives - Safonov, A. A.; Nosulenko, I. S.; Сафонов, Андрій Андрійович; Носуленко, Інна Степанівна; Сафонов, А. А.; Носуленко, И. С. (Запорізький державний медичний університет, 2021)
The process of studying free radicals began in the middle of the last century (the free radical theory of aging in 1956). Multiple studies have revealed the effect of free radicals on the cells of the body and the development of various diseases, such as diabetes, autoimmune diseases, diseases of the nervous system, and others. As a result, the term antioxidant has emerged, compounds that reduce and prevent the effects of free radicals. Most of the newly synthesized substances are studied for their antiradical properties. 1,2,4-Triazole derivatives are no exception, which has already proven themselves as biologically active compounds. The aim of this work was the investigation antiradical activity among 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol derivatives. Materials and methods. Previously synthesized 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol derivatives were used as test compounds. The research of antiradical activity was based on the interaction between 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4- triazole-3-thiol derivatives and 2,2-diphenyl-1-picrylhydrazyl (DPPH) in vitro. DPPH is a stable free radical. The color of its alcoholic solutions were intense purple (λmax = 517 nm). When DPPH interacted with compounds that were capable of scavenging free radicals, it produced products. These products are yellow in color and do not absorb light of the aforementioned wavelength. The study was carried out according to the method. Results. The antiradical activity of 10 new 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol derivatives was studied. Most of the test compounds show antiradical activity against DPPH. Compound 1 was the most active at a concentration of 1 × 10-3 M and the antiradical effect was close to ascorbic acid. Conclusions. The most active compound is 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol, which in a concentration of 1 × 10-3 M has an antiradical effect in 88.89 %. When reducing the concentration to 1 × 10-4 M, also reduces the antiradical activity to 53.78 %. Some conclusions are drawn regarding the “structure – effect” dependence between 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole- 3-thiol derivatives: – the introduction of 4-fluorobenzylidene radical (compound 2) into the 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol molecule results in a slight decrease in activity; – the introduction of 2-hydroxybenzylidene radical (compound 3) into initial molecule results a high antiradical effect, which hardly changes with decreasing concentration; – transformation to 2-((5-(thiophen-2-ylmethyl)-4-((R)amino)-4H-1,2,4-triazol-3-yl)thio)acetic acid has almost no effect on antiradical activity, except for compound 9 (the antiradical effect is reduse). Вивчення вільних радикалів розпочалося в середині минулого сторіччя (вільнорадикальна теорія старіння, 1956 р.). Численні дослідження виявили вплив вільних радикалів на клітини організму та розвиток у результаті цього різних захворювань: цукрового діабету, автоімунних захворювань, патологій нервової системи тощо. У зв’язку з цим з’явився такий термін, як антиоксиданти, на позначення сполук, що зменшують і запобігають впливові вільних радикалів. Більшість нових синтезованих речовин досліджують на наявність антирадикальних властивостей. Не є винятком похідні 1,2,4-тріазолу, що зарекомендували себе як біологічно активні сполуки. Мета роботи – дослідження антирадикальної активності серед похідних 4-аміно-5-(тіофен-2-ілметил)-4Н-1,2,4-тріазол-3-тіолу. Матеріали та методи. Дослідили синтезовані раніше похідні 4-аміно-5-(тіофен-2-ілметил)-4H-1,2,4-тріазол-3-тіолу. Дослідження антирадикальної активності засноване на взаємодії похідних 4-аміно-5-(тіофен-2-ілметил)-4H-1,2,4-тріазол-3-тіолу з 2,2-дифеніл-1-пікрилгідразилом (DPPH) in vitro. DPPH – стабільний вільний радикал. Колір його спиртових розчинів – інтенсивно-фіолетовий (λmax = 517 нм). Коли DPPH взаємодіє зі сполуками, що здатні вловлювати вільні радикали, він утворює комплекси. Ці сполуки мають жовтий колір і не поглинають світло з названою довжиною хвилі. Дослідження виконали згідно з методикою. Результати. Вивчили антирадикальну активність 10 нових сполук похідних 4-аміно-5-(тіофен-2-ілметил)-4Н-1,2,4-тріазол-3-тіолу. Більшість сполук виявляють антирадикальну активність щодо DPPH. Речовина 1 найбільш активна в концентрації 1 × 10-3 М, а її антирадикальний ефект близький до аскорбінової кислоти. Висновки. Найактивніша сполука – 4-аміно-5-(тіофен-2-ілметил)-4Н-1,2,4-тріазол-3-тіол, який у концентрації 1 × 10-3 М характеризується протирадикальною дією 88,89 %. При зниженні концентрації до 1 × 10-4 М антирадикальна активність знижується до 53,78 %. Зробили висновки щодо залежності «структура – антирадикальний ефект»: – введення 4-фторбензиліденового радикала (сполука 2) в молекулу 4-аміно-5-(тіофен-2-ілметил)-4Н-1,2,4-тріазол-3-тіолу призводить до незначного зниження активності; – введення 2-гідроксибензиліденового радикала (сполука 3) у вихідну молекулу спричиняє високий антирадикальний ефект, який майже не змінюється зі зменшенням концентрації; – трансформація до 2-((5-(тіофен-2-ілметил)-4-((R)аміно)-4Н-1,2,4-тріазол-3-іл)тіо)оцтової кислоти майже не впливає на антирадикальну активність, крім сполуки 9 (антирадикальний ефект суттєво знижується). Процесс изучения свободных радикалов начался еще в середине прошлого века (свободнорадикальная теория старения, 1956 г.). Многочисленные исследования показали влияние свободных радикалов на клетки организма и развитие в результате этого различных заболеваний: сахарного диабета, аутоиммунных заболеваний, патологий нервной системы и др. В связи с этим появился такой термин, как антиоксиданты, для обозначения соединений, уменьшающих и предупреждающих воздействие свободных радикалов. Большинство новых синтезированных веществ исследуют на антирадикальные свойства. Производные 1,2,4-триазола, которые уже зарекомендовали себя как биологически активные соединения, – не исключение. Цель работы – исследование антирадикальной активности производных 4-амино-5-(тиофен-2-илметил)-4H-1,2,4-триазол-3-тиола. Материалы и методы. В качестве тестируемых соединений использовали синтезированные ранее производные 4-амино-5-(тиофен-2-илметил)-4H-1,2,4-триазол-3-тиола. Исследование антирадикальной активности основано на взаимодействии производных 4-амино-5-(тиофен-2-илметил)-4H-1,2,4-триазол-3-тиола с 2,2-дифенил-1-пикрилгидразилом (DPPH) in vitro. DPPH – стабильный свободный радикал. Цвет его спиртовых растворов – интенсивно-фиолетовый (λmax = 517 нм). Когда DPPH взаимодействует с соединениями, которые способны улавливать свободные радикалы, образуются комплексы. Эти соединения жёлтого цвета и не поглощают свет с данной длиной волны. Исследование проведено согласно методике. Результаты. Изучено антирадикальное действие 10 новых соединений производных 4-амино-5-(тиофен-2-илметил)-4Н-1,2,4-триазол-3-тиола. Большинство исследуемых соединений проявляют антирадикальную активность в отношении DPPH. Вещество 1 наиболее активно в концентрации 1 × 10-3 М, а его антирадикальный эффект близок к аскорбиновой кислоте. Выводы. Самое активное соединение – 4-амино-5-(тиофен-2-илметил)-4Н-1,2,4-триазол-3-тиол, который в концентрации 1 × 10-3 М обладает антирадикальным действием 88,89 %. При снижении концентрации до 1 × 10-4 М антирадикальная активность снижается до 53,78 %. Сделаны выводы о зависимости «структура – антирадикальный эффект»: – введение 4-фторбензилиденового радикала (соединение 2) в молекулу 4-амино-5-(тиофен-2-илметил)-4Н-1,2,4-триазол-3-тиола приводит к незначительному снижению активности; – введение 2-гидроксибензилиденового радикала (соединение 3) в исходную молекулу приводит к высокому антирадикальному эффекту, который почти не меняется с уменьшением концентрации; – трансформация до 2-((5-(тиофен-2-илметил)-4-((R)амино)-4Н-1,2,4-триазол-3-ил)тио)уксусной кислоты почти не влияет на антирадикальную активность, кроме соединения 9 (антирадикальный эффект значительно снижается).
Антирадикальна активність нових похідних 4-аміно-5-(тіофен-2-ілметил)-4Н-1,2,4-тріазол-3-тіолу
Антирадикальная активность новых производных 4-амино-5-(тиофен-2-илметил)-4H-1,2,4-триазол-3-тиола
Сафонов А. А. - ORCID ID: 0000-0003-2861-1826; Носуленко І. С. - ORCID ID: 0000-0002-8725-7321
Keywords: antiradical activity; triazoles; heterocyclic compounds; антирадикальна активність; 1,2,4-тріазол; гетероциклічні сполуки; антирадикальная активность; 1,2,4-триазол; гетероциклические соединения